THE PHILOSOPHY FOUNDATIONS OF MARKETING THEORY AND RESEARCH - Negara, Danes Jaya (JURNAL BISNIS STRATEGI, 2003)
In marketing, there had been a simmering debate about its scientific status during the 1950s and 1960s but the Fall 1983 issue of the Journal of Marketing marked the start of this particular episode. This article provides the philosophy foundations of marketing thought at two centers of early development.Â  In particular is to evaluate scientific realism view and relativistic/contructionist view.Â  The author explores the nature of realism and relativism as it is currently being discussed in the philosophy of science. Scientific realism argues that truth is appropriate goal for marketing theory and research and that science can come to know the real word, though not with certainty. They argue that there is no grand theory of science. Relativists have long argued that there is no single method or approach to science. After addressing a fundamental premise of the entire debate, the author concludes that philosophically oriented marketing theorists need to further demonstrate the value of their work tor practicing marketing scientists.Â